Thermophysical properties of iridium at finite temperature *Project supported by the Department of Science and Technology–Fund for Improvement of Science and Technology Infrastructure Project (DST-FIST) (Level 1) of Department of Sciences and Technology (DST), New Delhi (Grant No. SR/FST/PST-001/2006). (30th September 2016) - Kumar, Priyank; Bhatt, N K; Vyas, P R; Gohel, V B
Abstract: The bulk properties of materials in an extreme environment such as high temperature and high pressure can be understood by studying anharmonic effects due to the vibration of lattice ions and thermally excited electrons. In this spirit, in the present paper, anharmonic effects are studied by using the recently proposed mean-field potential (MFP) approach and Mermin functional which arise due to the vibration of lattice ions and thermally excited electrons, respectively. The MFP experienced by a wanderer atom in the presence of surrounding atoms is constructed in terms of cold energy using the local form of the pseudopotential. We have calculated the temperature variation of several thermophysical properties in an extreme environment up to melting temperature. The results of our calculations are in excellent agreement with the experimental findings as well as the theoretical results obtained by using first principle methods. We conclude that presently used conjunction scheme (MFP+pseudopotential) is simple computationally, transparent physically, and accurate in the sense that the results generated are comparable and sometimes better than the results obtained by first principle methods. Local pseudopotential used is transferable to extreme environment without adjusting its parameters.